If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + -20 = 6x + 11 Reorder the terms: -20 + 3x = 6x + 11 Reorder the terms: -20 + 3x = 11 + 6x Solving -20 + 3x = 11 + 6x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6x' to each side of the equation. -20 + 3x + -6x = 11 + 6x + -6x Combine like terms: 3x + -6x = -3x -20 + -3x = 11 + 6x + -6x Combine like terms: 6x + -6x = 0 -20 + -3x = 11 + 0 -20 + -3x = 11 Add '20' to each side of the equation. -20 + 20 + -3x = 11 + 20 Combine like terms: -20 + 20 = 0 0 + -3x = 11 + 20 -3x = 11 + 20 Combine like terms: 11 + 20 = 31 -3x = 31 Divide each side by '-3'. x = -10.33333333 Simplifying x = -10.33333333
| 39-79=5(x-1) | | 251-w=186 | | 2(x+8)-3= | | 4b=15.65+3a | | 4x/40= | | 259=-v+149 | | .20+.15(70)=22.5 | | 3a+2b+2b=15.65 | | x+2x=.41 | | 2x-19+13x+33= | | |5x+10|=20 | | 2(w+4)+2(w)=104 | | 6(x-5)=8 | | 9h=2h-21 | | (2x-4)(x-3)=12 | | a=5.216666667+(2.666666667b) | | -20x+2=x-6 | | x^2+81=-49 | | |2x/3+8|=-20 | | x^2-5(7)+10= | | 3x^2+6x-7=2 | | -10+11t+7q-4t-3q+21= | | |1/3x-6|=15 | | log[2](12x+8)=2+log[2](x+3) | | 3a+(2b*4)=15.65 | | -5x^1= | | 8a-8=13(a-3) | | (-4x+3)+(2x+33)=96 | | 6y+2=8y+12 | | |-4x+2|=14 | | 3a+2b*4=15.65 | | m^2-20m-80=5 |